Peningkatan Kapasitas Remaja Untuk Mencegah Obesistas Melalui Kampanye Piringku Model T Sman 10 Kota Jambi - Putra, Egy Sunanda; Irfan, Ary (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Obesity is still a nutritional problem in developed and developing countries. Obesity or stomach disease occurs in adolescents aged >15 years. One of the efforts to prevent adolescent obesity is to control body weight through changes in eating patterns by promoting the slogan